PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TEMA PRISTIWA DALAM KEHIDUPAN PADA SISWA KELAS V SDN GADUNG DRIYOREJO GRESIK - Desi Eka Pratiwi (JIPD (Jurnal Inovasi Pendidikan Dasar), 2020)
This research aims to implement jigsaw learning models in primary school. This research is qualitative descriptive, The data of this research were collected using observation, test, and questionnaire. Based on research result, obtained data as follows: (1) teacher activity data get a percentage 82,3 % with the conversion of grades 81%-100% included in the excellent category. (2) student activity data get a percentage of 89,6% with the conversion of grades 81%-100% included in the category of very active. (4) the result of the questionnaire responses of students get a percentage of agree for 62% and disagree for 36%, student response data shows an increase. (4) classical learning outcomes get a percentage 87,24%, there are only 3 out of 29 students whose grades are below 75, so learning outcomes are included in the complete category. Keywords : Cooperative Learning, jigsaw, primary school